Bioinformatic analysis of endogenous and exogenous small RNAs on lipoproteins. Issue 1 (1st December 2018) - Allen, Ryan M.; Zhao, Shilin; Ramirez Solano, Marisol A.; Zhu, Wanying; Michell, Danielle L.; Wang, Yuhuan; Shyr, Yu; Sethupathy, Praveen; Linton, MacRae F.; Graf, Gregory A.; Sheng, Quanhu; Vickers, Kasey C.
ABSTRACT: To comprehensively study extracellular small RNAs (sRNA) by sequencing (sRNA-seq), we developed a novel pipeline to overcome current limitations in analysis entitled, "Tools for Integrative Genome analysis of Extracellular sRNAs (TIGER)". To demonstrate the power of this tool, sRNA-seq was performed on mouse lipoproteins, bile, urine and livers. A key advance for the TIGER pipeline is the ability to analyse both host and non-host sRNAs at genomic, parent RNA and individual fragment levels. TIGER was able to identify approximately 60% of sRNAs on lipoproteins and >85% of sRNAs in liver, bile and urine, a significant advance compared to existing software. Moreover, TIGER facilitated the comparison of lipoprotein sRNA signatures to disparate sample types at each level using hierarchical clustering, correlations, beta-dispersions, principal coordinate analysis and permutational multivariate analysis of variance. TIGER analysis was also used to quantify distinct features of exRNAs, including 5ʹ miRNA variants, 3ʹ miRNA non-templated additions and parent RNA positional coverage. Results suggest that the majority of sRNAs on lipoproteins are non-host sRNAs derived from bacterial sources in the microbiome and environment, specifically rRNA-derived sRNAs from Proteobacteria. Collectively, TIGER facilitated novel discoveries of lipoprotein and biofluid sRNAs and has tremendous applicability for the field of extracellular RNA.